Analysis of the Relationship Between Cost Stickiness and Financial Reporting Quality in the Indonesian Stock Exchange (Study in Manufacturing Sector Companies in 2018) - Tarisa Natakusumawati; Faisal Faisal (Diponegoro Journal of Accounting, 2021)
This study aims to determine the relationship between financial statements and cost stickiness in companies listed on the Indonesia Stock Exchange. The study used all data from manufacturing companies registered in Indonesia in 2018. The data collection method was carried out by means of documentation study and literature study. Data were analyzed using descriptive statistical tests, classical assumption tests, hypothesis tests, multiple regression analysis tests and goodness of fit tests, using the IBM SPSS 23 software. The results in this research showed that the raw material cost stickiness (MCA) had a significant positive effect on the level of disclosure of corporate financial statements (FRQ). However, administrative cost stickiness (ACA), sales cost stickiness (SCA) and labor cost stickiness (LCA) do not have a significant effect on the level of disclosure in the company's financial statements in the manufacturing sector.